Chronic Stress-Induced Gene Changes In Vitro and In Vivo: Potential Biomarkers Associated With Depression and Cancer Based on circRNA- and lncRNA-Associated ceRNA Networks - Zhou, Ting; Li, Mingming; Xiao, Zhijun; Cai, Jian; Zhao, Weiwei; Duan, Jingjing; Yang, Zhen; Guo, Zhijun; Chen, Yitian; Cai, Weijia; Huang, Piaopiao; He, Chaoyong; et al. (Frontiers in Oncology, 2021)
Circular RNAs (circRNAs) and long noncoding RNAs (lncRNAs) have been considered as biomarkers or regulators in many diseases. However, the exact role of circRNA or lncRNA mediated competing endogenous RNA (ceRNA) networks in the modulation of depression pathogenesis relevant processes is not clear. In this study, we profiled whole-transcriptome in depression patients’ blood samples via microarray analysis. As a result, a total of 340 circRNAs, 398 lncRNAs, 206 miRNAs and 92 mRNAs that were differentially expressed between the depression and control groups. Then we constructed ceRNA networks according to the differentially expressed genes (DEGs). by Using bioinformatics analysis, 89 pairs of circRNA-ceRNA and 49 pairs of lncRNA-ceRNA networks were obtained. Since depression is a broad and heterogeneous condition and that is known as a kind of promoter for many chronic diseases including cancer, so we further dug out 28 circRNAs, 61 lncRNAs, 26 miRNAs and 29 mRNAs that were are associated with cancer. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) GO and KEGG analyses showed that the DEGs were significantly enriched in cancer- related signaling pathways such as MAPK, Wnt, IL-17, Ras and PI3K-Akt signaling pathways. Genes involved in the above pathways such as S100A9, GATA2, SRFP5, SLC45A3, NTRK1, FRZB, has_circ_0014221, has_circ_0014220, has_circ_0087100 were dysregulated in various cancer cell lines by stress hormones inducing.ed HDC, GATA2 SLC45A3, NTRK1 were downregulated in tumor bearing mice explore to chronic unpredictable mild stress (CUMS). LncRNA mediated ceRNA network validation showed that over-expression of miR4530 declined HDC level. Our findings highlight the potential circRNAs and lncRNAs mediated ceRNA regulatory mechanisms in the pathogenesis of depression and as potential biomarkers in depression cancer comorbidity through the pathways of IL-17 or histidine metabolism.